2020
DOI: 10.1007/s00484-020-01965-2
|View full text |Cite
|
Sign up to set email alerts
|

Summer UTCI variability in Poland in the twenty-first century

Abstract: The paper analyses the temporal and spatial variability of the Universal Thermal Climate Index (UTCI) in Poland in summer. Summer is the season with the highest intensity of tourism traffic that is why it is important to determine biometeorological conditions, especially in popular tourist destinations such as coastal, mountain and urban areas, in the times of climate changes. The analysis was based on data from 18 stations of IMGW-PIB (Institute of Meteorology and Water Management-National Research Institute)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 49 publications
6
19
0
3
Order By: Relevance
“…However it should be noted that in winter UTCI values on the Polish coast decrease from west to east, and thus the degree of strain from cold stress in resorts in the western part of the coast is lower than in the Hel peninsula area (Koźmiński & Michalska, 2019). Strong heat stress most often (4% of days) appeared and lasted the longest (from the end of April to mid-September) in the south-east part of the country, in Busko-Zdrój, which confirms that the Upland Region is the warmest bioclimatic region of Poland (Krzyżewska et al, 2020). Very strong heat stress was only sporadically observed in the studied resorts, and in the highland resort of Krynica-Zdrój it was not recorded even once.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…However it should be noted that in winter UTCI values on the Polish coast decrease from west to east, and thus the degree of strain from cold stress in resorts in the western part of the coast is lower than in the Hel peninsula area (Koźmiński & Michalska, 2019). Strong heat stress most often (4% of days) appeared and lasted the longest (from the end of April to mid-September) in the south-east part of the country, in Busko-Zdrój, which confirms that the Upland Region is the warmest bioclimatic region of Poland (Krzyżewska et al, 2020). Very strong heat stress was only sporadically observed in the studied resorts, and in the highland resort of Krynica-Zdrój it was not recorded even once.…”
Section: Discussionmentioning
confidence: 55%
“…It was also confirmed that coastal resorts (represented in this study by Kołobrzeg) are the most privileged in thermal terms, as in the warm half of the year they have the most days in Poland with thermoneutral conditions (Kuchcik et al, 2013). Furthermore, in summer the Baltic coast is the coolest and most windy region of Poland (apart from highmountain areas) (Krzyżewska et al, 2020), which is reflected in the lowest frequency of strong heat stress in this region. In winter, meanwhile, cold stress occurred in Kołobrzeg far less often than in Busko-Zdrój and Krynica-Zdrój, while very strong cold stress was not observed there at all.…”
Section: Discussionmentioning
confidence: 99%
“…It should be emphasized that such a tendency is also projected for the future period, including discussed area (Schwarzak et al, 2014;Miszuk et al, 2016) and other European regions (Matzarakis et al, 2007;Oehler & Matzarakis, 2007). On the other hand, no statistically significant trends for heat stress were observed for the discussed area, whereas such tendencies occurred in some other Polish regions for previous periods (Półrolniczak et al, 2016;Krzyżewska et al, 2020;Tomczyk & Owczarek, 2020).…”
Section: Discussionmentioning
confidence: 67%
“…The spatiotemporal patterns of thermal exposure in a moderate-climate urban area were per-formed for a domain in Prague. The UTCI across Poland has been analyzed (Błażejczyk & Kunert, 2011;Błażejczyk et al, 2015b;Kuchcik 2017Kuchcik , 2020Owczarek, 2019;Tomczyk & Owczarek, 2020;Krzyżewska et al, 2020;Wereski et al, 2020;Kuchcik et al, 2021). The index has been also used to assess bioclimatic conditions in different regions in Poland (e.g., Nowosad et al, 2013;Milewski, 2013;Kolendowicz et al, 2018;Błażejczyk et al 2020;Głogowski et al, 2020) and in Polish cities (e.g., Błażejczyk et al, 2016;Bryś & Ojrzyńska, 2016;Bartoszek et al, 2017;Okoniewska, 2020;Kuchcik et al, 2021).…”
Section: Introductionmentioning
confidence: 99%